Profil Klinikopatologik Biopsi Massa Kolorektal di Instalasi Patologi Anatomi RSUD Arifin Achmad Provinsi Riau Periode Januari 2015 - Desember 2019 - Ilhami Romus; Khairun Nisa' (Fakultas Kedokteran Universitas Riau, 2021)
Colorectal masses can be non-neoplasm, benign neoplasm and malignant neoplasm. Diagnosis of colorectal mass can be done by biopsy or surgery then followed by histopathological examination. The aim of this study was to described the histopathology feature of colorectal mass biopsy in the Anatomic Pathology Laboratory of Arifin Achmad Regional Hospital in Riau Province January 2015 - December 2019. This study found 304 cases consisted of men (55,6%) and women (44,4%). The highest number of cases was in the 50-59 years age group (29,3%). The Malays (17,8%) was the largest ethnic group. The highest occupation was housewives (22%). Rectal tumor (73,1%) was the most common clinical diagnosis. The histopathological examination results of colorectal mass biopsy were non-neoplasm (26,7%), benign neoplasm (1,3%), and malignant neoplasm (72%). Adenocarcinoma was the most common biopsy histopathologic feature of malignant neoplasm (64,8%).